(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The aim of the present study was to evaluate the hypoglycemic activity of Gymnema sylvestre and Catharanthus roseus leaf extract in streptozotocin induced diabetic rats. Diabetes mellitus was induced by a single intraperitoneal injection of STZ (50 mgkg body weight). The experimental set up was formed as follows Group I – Normal Rats injected with normal saline is considered as vehicle control, Group II – Diabetic control administered with 20 Glucose Soln. for 14 days, Group III – STZ induced diabetic Wistar rats, administered with standard drug (Glibenclamide) 5 mgkg for 14 days, served as positive control, GROUPS-IV to IX STZ induced diabetic Wistar rats were orally administered with Aqueous, ethanolic and methanolic extracts of Gymnema sylvestre and Catharanthus roseus. Though there are many approaches to control diabetes and its secondary complications, herbal formulations are preferred due to lesser side effects and low cost. Gymnema sylvestre is a medicinal plant for the potential management of diabetes mellitus. The leaves are used in herbal medicinal preparation. The concerned study reveals the anti-diabetic potential of Gymnema sylvestre and Catharanthus roseus in controlling blood glucose level in Streptozotocin induced Diabetic rats. Gymnemic acid, a triterpenoid saponin in Gymnema sylvestre and Bioactive compounds like alkaloids (catharanthine, vindoline, vindolidine, vindolicine, vindolinine, vinblastine, vincristine, leurosine, and lochnerine), flavonoids, glycosides, flavonoids, triterpenoids, tannins, and steroids in Catharanthus roseus may be responsible for the significant stimulation of β-cells of pancreas in the production of Insulin. In the current work we have studied the anti-diabetic effect of the aqueous, ethanolic and methanolic extracts of Gymnema sylvestre and Catharanthus roseus on streptozotocin induced diabetic rats. Aqueous extract of G. sylvestre had significantly reduced the blood glucose level than the ethanolic and methanolic extracts. Similarly the ethanolic and methanolic extracts of Catharanthus roseus, has significantly reduced the blood glucose levels than the aqueous extract.